Kesiapan Hakim Pengadilan Agama Jember dalam Menyelesaikan Perkara Ekonomi Syariah Tahun 2012: The Readiness of Judges at the Jember Religious Court in Resolving Sharia Economic Cases in 2012 - M. Faisol (Fenomena, 2012)
The preparation of religious court judges in carrying out their new competencies to handle sharia economic conflicts is a top priority following the amendment of Law No. 7 of 1989 to Law No. 3 of 2006 concerning religious courts. This research was conducted to determine the readiness of religious court judges in Jember to resolve sharia economic issues as mandated by Law No. 3 of 2006. The results indicate that the judges at the Jember Religious Court are always prepared to handle sharia economic conflicts. However, the methods of examining, adjudicating, and resolving sharia economic cases have not yet been tested or measured, as no such cases have been reported to the Jember Religious Court since the enactment of Law No. 3 of 2006. Kesiapan hakim pengadilan agama dalam menjalankan kompetensi barunya untuk menangani konflik ekonomi syariah menjadi prioritas utama setelah perubahan Undang-Undang No. 7 Tahun 1989 menjadi Undang-Undang No. 3 Tahun 2006 tentang peradilan agama. Penelitian ini dilakukan untuk mengetahui kesiapan hakim pengadilan agama di Jember dalam menyelesaikan masalah ekonomi syariah sebagaimana diamanatkan dalam Undang-Undang No. 3 Tahun 2006. Hasil penelitian menunjukkan bahwa hakim pengadilan agama di Jember selalu siap dalam menangani konflik ekonomi syariah. Namun, cara memeriksa, memutus, dan menyelesaikan masalah ekonomi syariah belum teruji dan terukur, karena sejak diundangkannya Undang-Undang No. 3 Tahun 2006, belum ada satu pun perkara yang dilaporkan di pengadilan agama Jember.